Antecedents of behavior-based safety performance in the east coast of Malaysia small manufacturing enterprises - Nor Azma Rahlin
Each year the report from SOCSO highlighted that industrial accidents among the Small Medium Enterprises including small manufacturing enterprises, are higher compared to large companies. As a consequence, the financial issues related to industrial accidents are alarmingly high, making an empirical study for this industry highly appropriate to be investigated. Previous study devoted to proving that behavior can bring out the best of employees to improve safety. In respect of this, the present study integrat antecedents affecting Behavior-Based Safety Perfonnance. Antecedents in this study comprised of Work Ownership, Islamic Work Ethic, and Employee Safety Climate. This study intends to examine the effect of antecedents on Behavior-Based Safety Performance and the mediating effect of Employee Safety Climate in the relationship between exogenous constructs and endogenous constructs. A quantitative research approach has been applied for data collection, data measurements, and data analysis. In this study, 500 self-administered questionnaires have been given to the selected respondents in the small manufacturing enterprise using stratified random sampling in the east coast of Malaysia. Structural Equation Modelling on IBM SPSS AMOS version 22 software was used for the data analysis. The results revealed that two antecedents, which are Islamic Work Ethic and Employee Safety Climate, have a positive and significant effect on Behavior-Based Safety Performance, Interestingly, Employee Safety Climate has fully mediated the relationship between Work Ownership and Behavior-Based Safety Performance. Employee Safety Climate ha partially mediated the relationship between Islamic Work Ethic and Behavior-Based Safety Performance. The most important antecedent was Employee Safety Climate and even was a strong predictor of Behavior-Based Safety Performance. The results of this study demonstrated that improvement in Behavior-Based Safety Performance could be achieved by focusing on these antecedents. This study revealed that adaptive Behavior-Based Safety Performance measurement could serve as an alternative to safety performance measurement in small manufactming enterprises and, subsequently, reduce the number of industrial accidents in the Small Manufacturing Enterprises.